Farm crops and their relation to improved stock raising - Bealey, Jesse N. (My University, 1906)
Introduction: Our agricultural population is in need of more first class breeders of plants and animals. But there are only a few of our breeders who have done much to improve their stock. One who so improves his stock as to increase their productiveness has done much for his people. To become of value to the world as a breeder one must have energy and perseverance and an art and love for the business. He should start with that one breed of animals or plants which he best likes to work with, and stick to his work until good results come. Working always with one standard of excellence and a definite end in view. A great many of those who go into the business have but little knowledge of the laws of breeding and are not inclined to study or give any more of their attention to the work than will be necessary other farmer who is just as good a breeder but does not keep pedigree stock. Although we do not all have the art and ability to become stock improvers we can keep improved stock and without understanding all the practices and laws of breeding, if we would know and exercise the value feed and care has toward maintaining the excellencies of a herd, we can then afford to keep pure bred stock. In selecting a herd, after deciding upon the type or breed you wish to raise, select or have an expert stock judge select your herd from animals that can be bought at a reasonable price. Your bull should be the best that your means will allow. You can well afford to pay a large sum for a bull that shows good breeding and that will stamp his character upon his progeny. If you start out with improved stock or with fairly good stock, and expect to improve your herd, it will be necessary that you understand the influence of feed upon your stock.
Citation: Bealey, Jesse N. Farm crops and their relation to improved stock raising. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Animal Husbandry; Stock; Agriculture; Breeding; Theses